Peningkatan Keterampilan Pengelolaan Proyek Sistem Informasi Melalui Pelatihan Pembuatan Website Bagi Mahasiswa Universitas Muhammadiyah Jambi - Akbar, Zulfikri; Ikhsan, Muhammad; Helmina, Helmina; Dani, Rian; Hierdawati, Trie (Jurnal Suara Pengabdian 45, 2023)
This community service aims to enhance the information systems project management skills of students through website development training. The methods employed include initial study, planning, implementation, and evaluation. The results of the community service demonstrate the successful improvement of students' information systems project management skills through the training and website development activities. Evaluation using questionnaires reveals that all students rated the training as "good". Moreover, the community service proved to be effective in achieving the goal of enhancing students' skills. Recommendations include the continuation of sustained training, further exploration of theoretical concepts, collaboration with industry partners, and ongoing evaluation. The theoretical implications highlight the applicability of information systems project management concepts in website development.